Musykilah al-i’tidā ala al-mahārim fī Malaysia: tahqīqu ahammiyati qīmah al-isti’dzān fi al-islām wa jawānibuhā al-tarbawiyyah - Ali, Nurul Badriyah; Elatrash, Radwan Jamal Yousef (Fakultas Syariah, Institut Agama Islam Negeri (IAIN) Samarinda, 2017)
The problem of incest, including its incidence among Muslim societies, is one of the major legal cases faced by lawyers in Malaysia. Incest cases are often hidden because they are considered a disgrace of the family and society that cannot be forgiven. As a result, justice for the victims is difficult to enforce, and the case continues to occur because the law is considered not able to ensnare the perpetrators (deterrence effect). One researcher found that among the causes of incest is the ignorance of Islamic law in everyday life, especially in applying the values of "isti'dzān" (asking for permission). The concept of "isti'dzān can keep the soul and human behavior from falling into social problems. This is because the private territory (space and time) of family members, who live in the same house, including their modesty in dressed in the house, has been regulated by Shari`a in such a way. This paper is an analysis of the legal philosophy of the concept of "isti'dzān" in relation to the incidence of sexual intercourse, and the possibility of its application among Malaysian Muslim society. This paper concludes that applying the concept of asking permission to enter the private territory of family members living in the home is important to maintain the honor of each family member. This is very likely applied in Malaysian Muslim society through religious education on "isti'dzan" in schools or places of worship. With "isti'dzan" and keeping the modesty at home, it is expected that incidents of sexual intercourse can be prevented.